Chinese ink-facilitated fabrication of carbon nanotube/polyvinyl alcohol composite sheets with a high nanotube loading - Yan, W. L. (2014)
Fabricating carbon nanotube-based composites requires high degree of dispersion of carbon nanotubes into a polymer matrix. The widely used approaches reported in open literature for such a purpose are usually complicated and high-cost. Herein, we found that Chinese ink could be used to prepare composites composed of multi-walled carbon nanotubes (MWCNTs) and polyvinyl alcohol (PVA). The Chinese ink acted as a solvent and a dispersant. The MWCNT-ink-PVA ternary composite possessed both high flexibility and high electrical conductivity, with an optimized electrical conductivity of 8.17 S cm−1. This simple method is believed to be applicable to other nanosacle carbon materials.